Tools for teaching logic Third international congress, TICTTL 2011, Salamanca, Spain, June 1-4, 2011. Proceedings - Blackburn, Patrick; van Ditmarsch, Han; Manzano, María; Soler-Toscano, Fernando (Lecture Notes in Computer Science, 2011)
This book constitutes the proceedings of the Third International Congress on Tools for Teaching Logic, TICTTL 2011, held in Salamanca, Spain, in June 2011. The 30 papers presented were carefully reviewed and selected from 62 submissions.  The congress focuses on a variety of topics including: logic teaching software, teaching formal methods, logic in the humanities, dissemination of logic courseware and logic textbooks, methods for teaching logic at different levels of instruction, presentation of postgraduate programs in logic, e-learning, logic games, teaching argumentation theory and informal logic, and pedagogy of logic